The Impact of Household Pollutants and Fish Assemblages on the Environment of Some Internal Streams Fed by the Euphrates River, North of Basrah Province - Abdullah, Abdul Hussein J.; Aldoghachi, Mohammed A. (Mesopotamian Journal of Marine Sciences, 2024)
This study was conducted in response to a lack of research in the region and aims to evaluate the impact of household pollutants and fish populations on the environment and investigate their role in the disappearance of some ancient phenomena that occur annually. The study was performed from January to December 2023 on the internal streams fed by the Euphrates River in Al-Sadiq District, north of Basrah Province. Some ecological parameters were measured: water temperature, salinity, hydrogen ion concentration, dissolved oxygen, biological oxygen demand, total nitrate, and phosphate. Out of the total of 17 fish species nine of them were native, and eight were exotic species belonging to 15 genera, nine families, and five orders, all of them affiliated with the bony fish Osteichthyes class. Four species recorded the highest values of numerical relative abundance and formed 78.01% of the overall number of species. The current study concluded that the region has moderate total nitrate and phosphate concentrations and that the fish assemblage contributes to the recovery from eutrophication by fish feeding on filamentous algae and aquatic plants.